Language strategies in tourism branding: A case study of website Dinas Parwisata Kabupaten Mandailing Natal - Batubara, Muhammad Hasyimsyah (Privietlab, 2025)
In the digitalization era, language strategy has become an important part of tourism brands to enhance a destination's appeal and image. This study examines the language on the Mandailing Natal Regency Tourism Office Website (https://pariwisata.madina.go.id/), which is used for tourism branding. The research method used is qualitative descriptive analysis with a critical text analysis approach, including data collection from website content. The study results indicate that the language used on this website has several shortcomings, such as less attractive narratives, inconsistent language style, a lack of emphasis on local identity, and a suboptimal information structure. In addition, the visual elements on the website are not supported by relevant narratives. This means that the potential of Mandailing Natal Regency tourism branding has not been fully utilized using a language strategy. They could do a better job with language style consistency, local feeling emphasis, and findability elements. The findings of this study offer strategic recommendations for improving website quality and advancing tourism communication strategies.